Comparative Analysis of Soft Pneumatic Actuator Designs for Effective Human Finger Movement: A Study on Continuous and Non-Continuous Chamber Configurations - Ritonga, Syahirul Alim; Herianto (LPPM Politeknik Aceh Selatan, 2023)
Soft actuators show immense potential in various fields, such as wearable medical devices and the rehabilitation of stroke patients. This study aims to design and fabricate a soft pneumatic actuator (SPA) that effectively mimics human finger movements, with specific focus on post-stroke rehabilitation. Two SPA designs, referred to as M1 and M2, were developed and compared. M1 featured segmented chambers to mimic finger joints, while M2 had continuous chambers. The performance of the SPAs was evaluated based on curvature, generated force, and similarity to natural finger movement. Results showed that M1 exhibited superior curvature and achieved greater bending angles compared to M2 at the same pressure levels. This makes M1 well-suited for applications requiring high bending angles such as gripping. Additionally, M2 demonstrated the ability to mimic specific angles associated with picking-like movements. The findings highlight the potential for further research to explore the customization of SPAs for specialized tasks by modifying the number of sections and chambers. In terms of force, M2 generated slightly higher forces than M1, although the difference was not statistically significant. Overall, it is expected that this research contributes to the development of soft actuators and wearable medical devices, particularly in the field of post-stroke rehabilitation.